MENINGKATKAN SDM MASYARAKAT DAN PEMUDA PEMUDI DALAM MECIPTAKAN DESA SONOWANGI YANG INOVATIF, KREATIF DAN SOLUTIF SERTA MENJADIKAN DESA YANG MANDIRI - Kukuh Santoso (VICRATINA, 2019)
The research objectives were to re-create the spirit of the community and young people in advancing an independent village, find out the obstacles faced in the village and to offer solutions. the data collection technique was done by interview and direct observation. The results showed that: Lack of awareness among young people and the community in mutual cooperation activities such as community service, signposts, and entrepreneurship seminars aimed at advancing the village. This research involved youth from the Youth organization and also the village community. Various activities were well organized but also inseparable from various obstacles such as the problem of compactness. Awareness from all elements of society that mutual cooperation activities are the responsibility of youth and society with the aim of creating an innovative, creative and solution village.